2009
DOI: 10.17221/1765-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial oil and fish oil on rumen fermentation and metabolism of fatty acids in artificial rumen

Abstract: The objective of this study was to examine the effect of microbial oil (MO, n-6 fatty acids) and fish oil (FO, n-3fatty acids) used in their blends as supplements (5% wt/wt) to the diet containing 80% of hay and 20% of barley on rumen fermentation and lipid metabolism in artificial rumen. Overall, three different ratios of n-6 and n-3 fatty acids (1:1, 3:1, and 5:1) as the blends of MO and FO were used. Two similar consecutive experiments were carried out within 2 months. Each experiment lasted for 12 days wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Aside from the animal factors, like the breed, parity or stage of lactation (Jensen, 2002;Kelsey et al, 2003;Pietrzak-Fiećko et al, 2009), the nutrition substantially determines the FA composition in the milk fat (Jenkins and McGuire, 2006;Strusińska et al, 2006;Hanuš et al, 2008;Liu et al, 2008;Jalč et al, 2009;Kudrna et al, 2009;Veselý et al, 2009). The addition of forage, especially of fresh grass, into feeding rations was found to enhance the proportion of unsaturated FAs in cow milk fat compared to saturated FAs (Dewhurst et al, 2006;Elgersma et al, 2006).…”
mentioning
confidence: 99%
“…Aside from the animal factors, like the breed, parity or stage of lactation (Jensen, 2002;Kelsey et al, 2003;Pietrzak-Fiećko et al, 2009), the nutrition substantially determines the FA composition in the milk fat (Jenkins and McGuire, 2006;Strusińska et al, 2006;Hanuš et al, 2008;Liu et al, 2008;Jalč et al, 2009;Kudrna et al, 2009;Veselý et al, 2009). The addition of forage, especially of fresh grass, into feeding rations was found to enhance the proportion of unsaturated FAs in cow milk fat compared to saturated FAs (Dewhurst et al, 2006;Elgersma et al, 2006).…”
mentioning
confidence: 99%
“…The types of PCS affecting carbohydrate metabolism can partly explain the variation among treatments in the individual SCFA. When diets with direct supplementation of microbial oil (i.e., GLA-enriched oil; 30 g · kg −1 DM) or microbial oil blends are incubated, the molar proportion of acetate is reduced whereas the molar proportion of propionate increases (Jalc et al, 2005;Jalč and Čertík, 2005;Jalč et al, 2009). However, diet supplementation with PCS reduced especially the molar proportion of n-butyrate.…”
Section: Impact On Ruminal Fermentation Parametersmentioning
confidence: 99%
“…It is well known that the majority of CLA isomers in ruminant-derived food products originate from the isomerization of 18:2n-6 and 18:3n-3 in the rumen (reactions proceed via different mechanisms catalysed by bacterial enzymes); however, diet is the principal determinant of the amount and distribution of CLA isomers formed in the rumen (Shingfield and Wallace, 2014). Diets supplemented directly with PUFA-enriched oils increased the production of TVA and CLA, resulting in incomplete FA biohydrogenation (Jalc et al, 2005;Jalč et al, 2009;Szumacher-Strabel et al, 2009). Butyrate-forming populations in the rumen are highly active in the biohydrogenation of PUFAs (Newbold et al, 2001), but in experiments presented in the review a clear decrease in n-butyrate values was shown.…”
Section: Impact On Lipid Metabolismmentioning
confidence: 99%
“…In addition, direct effects of microbial oil (30 g/kg; w/w) or oil blends (microbial and fish oil) on lipid metabolism in the RUSITEC effluent cause the incomplete BH of unsaturated fatty acids with an increase in TVA concentration (Jalč et al, , 2009). None of the WB diets enriched with GLA (i.e.…”
Section: Fatty Acids and Biohydrogenationmentioning
confidence: 99%
“…Previously we tested direct effects of only microbial oil produced by T. elegans on rumen metabolism in vitro and incomplete biohydrogenation of FA was found Jalč et al, , 2009. Therefore the objective of the present in vitro study was to examine the effects of T. elegans prefermented cereals such as wheat bran/spent malt grains (LH+WB+TE), wheat bran/spent malt grains enriched with sunflower oil (LH+WB+SO+TE) or ground maize grains (LH+GC+TE) on the rumen metabolism in an artificial rumen.…”
mentioning
confidence: 99%